Effects of nanoparticle migration on non-Newtonian nanofluids in a channel with multiple heating and cooling regions. (April 2017) - Li, Botong; Zhang, Wei; Zhu, Liangliang; Lin, Yanhai; Bai, Bin
Highlights: Nanofluid based power-law flow in a channel with multiple heaters is investigated. Viscosity and thermal conductivity are determined by particle concentration. Results of homogeneous and inhomogeneous nanoparticle distribution are different. Particle distribution plays an important part in thermal performance of nanofluids. The numerical technology presented here is applicable to more general cases. Abstract: Laminar forced convection nanofluids based non-Newtonian flow in a horizontal parallel channel with multiple regions of heating and cooling are investigated, taking into account the inhomogeneous distribution of nanoparticles. The non-Newtonian behaviour of nanofluids is described by the power-law model. The velocity, temperature and concentration fields, heat transfer coefficient ratio, and pressure drop are obtained numerically by solving the coupled momentum, energy and concentration equations. Results based on assumption of homogeneous and inhomogeneous distribution of nanoparticles are compared with each other. It is found that the detailed information of velocity, temperature and pressure drop obtained by these two opposite assumptions are largely different. The non-uniform distribution of nanoparticles has a much weaker influence on temperatures compared to the uniform distribution; and the non-uniform distribution of nanoparticles in the base fluid results in a smaller pressure drop than the uniform cases do. The above findings highlight the necessity and significance of studying the effects of nanoparticles' sedimentation and precipitation on heat and mass transfer for related industrial applications. And the thermal performance of power-law nanofluids investigated in this paper may shed some light on more efficient design of heat exchangers.